Does Forced Plant Maturation by Applying Herbicide with Desiccant Action Influence Seed Longevity in Soybean? - Larissa Chamma; Gustavo Ferreira da Silva; Samara Moreira Perissato; Cleonei Alievi; Prínscilla Pâmela Nunes Chaves; Valéria Cristina Retameiro Giandoni; Juliano Carlos Calonego; Edvaldo Aparecido Amaral da Silva (Plants, 2023)
Herbicides with desiccant actions may be used to anticipate the harvesting of soybean seeds. This technique aims to minimize the negative influence of biotic and abiotic factors on seed physiological quality at the end of the plant cycle. However, forced seed maturation with the application of herbicides can compromise the acquisition of seed quality components, especially longevity. Thus, the objective of this research was to evaluate the physiological quality of soybean seeds subjected to forced maturation with desiccants. The experiment was performed in a completely randomized design, with a treatment consisting of soybean plants subjected to the application of herbicides with desiccant action at stage R7.3 and another that underwent the natural process of maturation, that is, without herbicide application. The herbicide used was Paraquat. Seed germination, vigor (first germination count, dry mass, seedling length, time to reach 50% germination(t50), emergence index, and emergence speed), and longevity(P50) were evaluated. The herbicides did not affect germination (normal seedlings). However, the acquisition of vigor and longevity, and the preservation of seed vigor during storage were affected. Thus, the results indicate that the application of herbicide with desiccant action interrupts the process of acquisition of seed physiological quality, notably longevity in soybean seeds.